THE TRADITIONAL FOLK CALENDAR OF THE URAL GERMANS IN THE XX-XXI CENTURIES - Vayman, D.I. (Perm Federal Research Centre Journal, 2016)
The article considers the development of calendar rites of the Ural Germans in the XX century, which is based on the field ethnographic research, held among German inhabitants of Perm Krai, the Republic of Bashkortostan and Orenburg and Chelyabinsk Oblast. Structural changes of the calendar and its key directions at the beginning of the XXI century are determined.